A hero perished : the diary and selected letters of Nile Kinnick - Kinnick, Nile C. (Nile Clarke), 1918-1943 (University of Iowa Press, 1991)
A Hero Perished tells Nile Kinnick's story. This grandson of an Iowa governor, the son of parents who disciplined him to strive for his measure of greatness, became a Heisman Trophy winner and national celebrity through a combination of talent and circumstance. Following his college successes, Kinnick began legal study to prepare for a political career, but with the approach of war he entered the Navy Air Corps to refashion himself as a fighter pilot. Assigned to the carrier USS Lexington on its premier cruise, he took off in a defective plane & mdash;and his death shocked a nation grown.